Explaining Ethnic Differentials in COVID-19 Mortality: A Cohort Study. Issue 2 (29th September 2021) - Batty, G David; Gaye, Bamba; Gale, Catharine R; Hamer, Mark; Lassale, Camille
Abstract: Ethnic inequalities in coronavirus disease 2019 (COVID-19) hospitalizations and mortality have been widely reported, but there is scant understanding of how they are embodied. The UK Biobank prospective cohort study comprises approximately half a million people who were aged 40–69 years at study induction, between 2006 and 2010, when information on ethnic background and potential explanatory factors was captured. Study members were prospectively linked to a national mortality registry. In an analytical sample of 448, 664 individuals (248, 820 women), 705 deaths were ascribed to COVID-19 between March 5, 2020, and January 24, 2021. In age- and sex-adjusted analyses, relative to White participants, Black study members experienced approximately 5 times the risk of COVID-19 mortality (odds ratio (OR) = 4.81, 95% confidence interval (CI): 3.28, 7.05), while there was a doubling in the South Asian group (OR = 2.05, 95% CI: 1.30, 3.25). Controlling for baseline comorbidities, social factors (including socioeconomic circumstances), and lifestyle indices attenuated this risk differential by 34% in Black study members (OR = 2.84, 95% CI: 1.91, 4.23) and 37% in South Asian individuals (OR = 1.57, 95% CI: 0.97, 2.55). The residual risk of COVID-19 deaths in ethnic minority groups may be ascribed to a range of unmeasured characteristics and requires further exploration.